Peran Musik Tradisi Kelintang Tungkal Sebagai Prosesi Malam Beinai Masyarakat Kampung Nelayan Kabupaten Tanjung Jabung Timur - Gunawan, Indra; Bahar, Mahdi; Aulia, Defni (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to know the role of the Kelintang Tungkal music tradition as a musical tradition that lives and develops in the Kampung Nelayan Sub-District as a form of social integration and a developing musical structure. The structure is seen from the perspective of anthropologogical music, that Kelintang Tungkal was originally used by the community as accompaniment music in medical ceremonies but at this time the ceremony was no longer played because the myth of the local community that rolled the Kelintang Tungkal community had a strong magical element, so that these types of blows may not be made or played anywhere. Then the local community changed the function of the Kelintang Tungkal as an entertainment activity for the local community at wedding parties, welcoming traditional guests and as dance accompaniment music. Most of the data collected in this study were obtained from research on places and performances, interviews, and references related to writing about tungkal latitude, and were analyzed with qualitative approach. This study concludes that there has been a change in the Kelintang Tungkal performance that was originally used for medical ceremonies, because the functional factor of the Kelintang Tungkal performance turned into entertainment.